DISTRIBUTION OF PELAGIC FISH IN SOUTH CHINA SEA USING GEOSTATISTICAL APPROACH - Hidayat, Esa Fajar; Pujiyati, Sri; Suman, Ali; Hestirianoto, Totok (Jurnal Ilmu Kelautan SPERMONDE, 2018)
Pelagic fish are spesies that live in water column at depth of 100 to 200 meters from surface. They migrate as a group looking for nutrient and spawning place. Potential fisheries comodities in Indonesia including pelagic fish have high economic value. Then, stock assessment of pelagic fish measurement is important to researched. The research was conducted in May – June 2016 surrounding South China Sea waters using Madidihang 02 Research Vessel operated by Marine Fisheries Affair (MFA) Republic of Indonesia. To estimate the density of pelagic fish hydro-accoustic equipment and oceanography parameters were used and measured during the campaign. The split beam echosounder was use in aim to obtain precission position and number of fish target. The highest density of fish was found around Tambelan Island and Anambas Island. Statistically pelagic fish density has correlation with chlorophyll-a, salinity, temperature, and sea current velocity. The statistical analysis between pelagic fish density and those oceanography parameters (as statistic variables) yields positive vector correlation.